Investigations of segmental arterial stiffness in a cross‐sectional study on young adult male trained swimmers, cyclists, and non‐trained men - Masato Nishiwaki; Daisuke Kume; Naoyuki Matsumoto (Physiological Reports)
Abstract Contrary to cardiovascular risk reductions by aerobic exercise, arterial stiffness, as assessed by brachial‐ankle pulse wave velocity (PWV), is higher in swimmers and controls than in other aerobically trained individuals. The main muscles actively recruited in swimming are in the upper limbs, so this study aimed to investigate heart‐brachial PWV in swimmers and to compare arterial stiffness indices between modes and measurement localities. Subjects comprised 60 individuals (18–22 years), including 20 untrained controls (Con), 20 aerobically trained cyclists (Aero), and 20 swimmers (Swim). Characteristics and strength did not differ, but peak oxygen uptake was significantly higher in Aero and Swim than in Con. Brachial‐ankle PWV was significantly lower in Aero than in Con and Swim and no significant difference was observed between Con and Swim (Con, 1070 ± 115; Aero, 916 ± 109; Swim, 1035 ± 91 cm/s). Nevertheless, heart‐brachial PWV was significantly lower in Swim than in Con and tended to be lower in Swim than in Aero (Con, 344 ± 25; Aero, 330 ± 41; Swim, 308 ± 31 cm/s). Heart‐ankle PWV was significantly lower in both Swim and Aero than in Con (Con, 618 ± 47; Aero, 580 ± 54; Swim, 576 ± 43 cm/s). Therefore, these findings indicate that swimmers can develop segment‐specific reductions in heart‐brachial arterial stiffness, unlike aerobically trained cyclists.